2022
DOI: 10.1098/rsos.211855
|View full text |Cite
|
Sign up to set email alerts
|

Language acquisition and speech rhythm patterns: an auditory neuroscience perspective

Abstract: All human infants acquire language, but their brains do not know which language/s to prepare for. This observation suggests that there are fundamental components of the speech signal that contribute to building a language system, and fundamental neural processing mechanisms that use these components, which are shared across languages. Equally, disorders of language acquisition are found across all languages, with the most prevalent being developmental language disorder (approx. 7% prevalence), where oral langu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 96 publications
(145 reference statements)
2
23
0
1
Order By: Relevance
“…We also demonstrate transfer-learning of EEG features for identification of children with dyslexia across different receptive speech tasks and different samples of children. Taken together, our data provide robust evidence for a temporal sampling deficit in two developmental disorders of language learning, dyslexia and DLD [10,45].…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…We also demonstrate transfer-learning of EEG features for identification of children with dyslexia across different receptive speech tasks and different samples of children. Taken together, our data provide robust evidence for a temporal sampling deficit in two developmental disorders of language learning, dyslexia and DLD [10,45].…”
Section: Discussionsupporting
confidence: 60%
“…Further, we have shown that low-frequency oscillatory activity during speech listening can reliably classify children with dyslexia. These data suggest that mechanistic relationships between low frequency (i.e., delta and theta) oscillatory bands are fundamental to understanding the aetiology of dyslexia and DLD, as predicted by TS theory [10, 45]. The data also show the importance of studying children when trying to understand causal factors in developmental disorders of learning.…”
Section: Discussionmentioning
confidence: 83%
“…LFP centre frequencies were filtered from 2 to 8 Hz, in 1 Hz steps with a 2 Hz bandwidth, and HFA centre frequencies were filtered from 17.5 Hz to 42.5 Hz, in 5 Hz steps with a 5 Hz bandwidth before a normalised modulation index value was computed for each channel (19,42). The EEG bands were defined as delta (2-4 Hz), theta (4-8 Hz) beta (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) and gamma (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45). The channel exhibiting the strongest nMI, within predefined phase and amplitude band groupings (delta/beta, delta/gamma, theta/beta, theta/gamma), was taken forward for further analysis.…”
Section: Phase Amplitude Coupling (Pac)mentioning
confidence: 99%
“…The developmental theoretical framework encapsulated by TS theory informed Araujo et al's (27) modelling (Pre-print), and predicts that cortical tracking within specific low-frequency bands (i.e. delta, 1-4 Hz and theta, 4-8 Hz) and their interactive dynamics is central to language acquisition (4,28,29). In brief, if low-frequency cortical tracking and/or dynamic relations between frequency bands are atypical, then developmental trajectories for language may also be atypical.…”
Section: Introductionmentioning
confidence: 97%
“…TS theory now provides a systematic sensory/neural/cognitive framework for explaining childhood language disorders [27]. TS theory proposes that accurate sensory/neural processing of the amplitude envelope of speech is one foundation of language acquisition, and that impairments in discriminating key aspects of the envelope such as amplitude rise times at different temporal rates (which relate to speech rhythm) is one cause of developmental language disorders [28]. The amplitude envelope of any sound is the slower changes in AM (intensity or signal energy) that unfold over time.…”
Section: Introductionmentioning
confidence: 99%